Pengalih Fungsian Lahan Pertanian Ke Non Pertanian Di Kabupaten Tegal - Laeli Nurchamidah (Jurnal Akta, 2017)
ABSTRACT Research on "Functional Distribution of Agricultural Land into Non-Agriculture in Tegal Regency" aims to determine the factors behind, the procedure and the impact of the conversion of agricultural land to Non agricultural in Tegal regency.As in other areas throughout Indonesia, the conversion of agricultural land to non-agricultural in Tegal regency is one of the problems faced. The transfer of agricultural land to non-agriculture is caused by several factors such as demographic factors or rapid population growth, economic factors, change of mindset and behavior factors, and agricultural production process factors that are not balanced with the results obtained. The procedure for the submission of the conversion of agricultural land to non-farm in Tegal regency is basically related to the permit of whether or not the conversion of agricultural land to non-agricultural land is done. This is due to the great impact of the land conversion. These impacts, among others, threatened food security and socio-cultural impact of the shift of agrarian society as a cultural feature of Indonesian society into industrial society.Keywords: Function Transfer, Agricultural land, non agricultural land ABSTRAKPenelitian tentang “Pengalih Fungsian Lahan Pertanian Ke Non Pertanian di Kabupaten Tegal” bertujuan untuk mengetahui faktor-faktor yang melatarbelakangi, prosedur dan dampak pengalih fungsian lahan pertanian ke Non pertanian di Kabupaten Tegal.Seperti halnya di wilayah lain di seluruh Indonesia, alih fungsi lahan pertanian ke non pertanian di wilayah Kabupaten Tegal merupakan salah satu permasalahan yang dihadapi. Alih fungsi lahan pertanian ke non pertanian disebabkan oleh beberapa faktor antara lain faktor demografi atau pertumbuhan penduduk yang sangat cepat, faktor ekonomi, faktor perubahan pola pikir dan perilaku, serta faktor proses poduksi pertanian yang tidak seimbang dengan hasil yang didapatkan. Prosedur untuk pengajuan pengalih fungsian lahan pertanian ke Non pertanian di Kabupaten Tegal pada dasarnya berkaitan dengan perizinan dapat tidaknya alih fungsi lahan pertanian ke non pertanian tersebut dilakukan. Hal ini mengingat dampak yang besar dari adanya alih fungsi lahan tersebut. Dampak tersebut antara lain terancamnya ketahanan pangan dan dampak sosial budaya masyarakat yaitu bergesernya masyarakat agraris sebagai ciri budaya masyarakat Indonesia menjadi masyarakat industri.Kata Kunci : Alih Fungsi, Lahan pertanian, lahan non pertanian